The Wrong Rite of Passage: Comparing Sex Trafficking to Other Types of Child Maltreatment Using the National Child Abuse and Neglect Data System (NCANDS) - Branscum, Caralin (Victims & offenders, 2023)
Using the 2019 National Child Abuse and Neglect Data System, the prevalence and predictors of substantiated reports of child sex trafficking (CST) (n = 1,286) and other maltreatment (n = 705,778) (e.g., physical abuse, sexual abuse, but not sex trafficking) were explored. Descriptive statistics were used to present the profile of children who were victims of CST, and negative binomial regression modeling explored the individual/ontological-, microsystem-, and exosystem-level risk factors for CST compared to other forms of maltreatment. Findings showed that multiracial identity, substance use, disability status; caregiver type—most notably living in a group home—and residing in more rural areas; and professionals as the reporting source were associated with CST versus other maltreatment. Implications for research, policy, and practice for CST are discussed.